Transformasi Konsep Diri Jamaah Haji (Studi Fenomenologi pada Kelompok Bimbingan Ibadah Haji Lembaga Haji Muhammadiyah Jawa Barat) - Imron Rosyidi; Encep Dulwahab (State Institute of Islamic Studies (IAIN) Salatiga, 2019)
Hajj is one of the most complex worship services. Not only does it requirepsychic and physical strengths, but it also requires comprehensive and consistentunderstanding and experience. Many changes in self occur in the congregationwhen the pilgrimage. This is the purpose of this research, which is to find out thetransformation of the hajj pilgrims’ self-concept before and after the Hajj. Byusing a qualitative method of the phenomenological perspective, the results ofthis research indicate that there are several self-concepts of pilgrims, including:prospective hajj pilgrims are not good at reciting, hajj candidates are less closeto the Khaliq, and hajj candidates have less concern for others. In addition,there is a self-concept of pilgrims after Hajj. There is a transformation of self-image with a “new status” as a hajj mabrur as a way to make oneself deserve tobe called Hajj with frequent prayers in congregation in the mosque and caringfor others